2015
DOI: 10.5713/ajas.15.0796
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Contribution of Poultry and Pig Production to Greenhouse Gas Emissions in South Korea Over the Last 10 Years (2005 through 2014)

Abstract: The goal of this study was to estimate the emissions of greenhouse gases (GHG), namely methane (CH4), nitrous oxide (N2O), and carbon dioxide (CO2) from poultry and pig production in South Korea over the last 10 years (2005 through 2014). The calculations of GHG emissions were based on Intergovernmental Panel on Climate Change (IPCC) guidelines. Over the study period, the CH4 emission from manure management decreased in layer chickens, nursery to finishing pigs and gestating to lactating sows, but there was a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…On the other hand, carbon sources refer to carbon emissions and are seen as undesirable outputs [17,18]. Among them, some scholars discussed agricultural carbon emissions from a single-dimensional perspective, such as planting [17][18][19][20], livestock and poultry breeding [19][20][21][22][23][24][25] and fishery production [26][27][28][29]. Some scholars integrated multidimensional carbon sources for investigation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, carbon sources refer to carbon emissions and are seen as undesirable outputs [17,18]. Among them, some scholars discussed agricultural carbon emissions from a single-dimensional perspective, such as planting [17][18][19][20], livestock and poultry breeding [19][20][21][22][23][24][25] and fishery production [26][27][28][29]. Some scholars integrated multidimensional carbon sources for investigation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Results of [75] [76]. Authors [77] found very low N 2 O emissions in the housing of broilers, which were on the level of the detecting threshold of their measuring device.…”
Section: Emissions From Hen and Broiler Housingmentioning
confidence: 99%
“…Livestock production has been noted as the largest source of methane from agriculture [3], with enteric D DAVID PUBLISHING…”
mentioning
confidence: 99%